Hubungan Kualitas Website, Kepercayaan dan Niat untuk Menggunakan pada Penggunaan E-Government: Studi Kasus Sistem Informasi Ketenagakerjaan (Sisnaker) - Ivan Lilin Suryono (Jurnal Ketenagakerjaan, 2021)
The development of technology and information results in changes for the government in providing services to related stakeholders. The Ministry of Manpower has specifically provided employment services by building manpower information system (SISNAKER) that can be accessed online. This study aims to analyze relation the quality of the website which affects the intention to use Sisnaker. Data were collected using an online survey of 2041 Sisnaker users. Data processing is carried out using the Structural Equation Model (SEM) method. Based on the results, the website quality factor (with the biggest aspect of website content) has a positive effect on trust, and trust has a positive influence on the intention to use the service. The Ministry of Manpower need improve the quality of web sites on the aspects of content, ease and improve responsiveness to be able to increase the trust and the number of service users.